Cultivation of Jatropha curcas L. leads to pronounced mycorrhizal community differences. (October 2015) - Dieng, Amadou; Duponnois, Robin; Ndoye, Ibrahima; Baudoin, Ezékiel
Abstract: Plantations of Jatropha curcas for biodiesel production in tropical and sub-tropical regions are currently booming. Although Jatropha species are well known for synthesizing a range of toxicants, the effects of J. curcas monoculture on the symbiotic status of staple crops and trees have hardly been investigated. We transferred to the greenhouse soil samples collected from 3 J. curcas plantations established 1, 2 and 15 years ago in Senegal, together with soil samples from the corresponding adjacent fallow plots. We tested whether the modification of the original chemical and microbial soil properties induced by the development of J. curcas could alter the growth of common local crops (millet, cowpea) and of a local tree ( Acacia seyal ), all grown in pots. We also investigated effects at the scale of the root mycorrhizal community by determining root colonization patterns (frequency, intensity) and taxonomic diversity (18S rDNA sequencing). Pronounced compositional shifts in root mycorrhizal communities were almost systematically observed between Glomeraceae and Gigasporaceae, or in some cases within Glomeraceae. Biomass and N–P shoot contents were often higher in J . curcas -grown soils. In conclusion, the altered composition of the soil mycorrhizal communities in response to the development of J. curcas did not have detrimental effects on local staple crops. The functional consequences of such modified mycorrhizal assemblages should now be further investigated under more stressful conditions. Highlights: We examined how Jatropha curcas -cultivated soils impact on the mycorrhization of local crops. Shifts in the composition of the root AMF community were systematically detected. Growth performance and mycorrhization intensity of trap cultures were not altered. The effects of J. curcas were not correlated with plantation age.